Clinical efficacy assessment in severe vernal keratoconjunctivitis: preliminary validation of a new penalties-adjusted corneal fluorescein staining score - Leonardi, Andrea (J Mark Access Health Policy, 2020)
Introduction and objective: Vernal keratoconjunctivitis (VKC) is a rare allergic eye condition that occurs in children and is characterised by a combination of debilitating symptoms. Repeated use of topical corticosteroid rescue therapy is often necessary in severe forms. This study aims to assess the validity of a new composite endpoint: the penalties-adjusted corneal staining score (PACS-S) proposed as primary endpoint in VEKTIS trial evaluating the efficacy of a new corticosteroid-sparing treatment, VERKAZIA® (ciclosporin 1 mg/ml eye drops), in severe VKC patients. Methodology: This research comprised a systematic literature review to identify efficacy endpoints being proposed in clinical trials for pediatric patients with severe VKC, followed by a remote expert advisory board assessing the validity of the PACS-S. Results: While no agreed or validated endpoint for assessing efficacy in VKC was identified when VEKTIS trial started, the experts’ board acknowledged a high face validity of PACS-S as a subjective integrated measure matching the current clinical practice. A fair external validity was considered with regards to VEKTIS trial secondary endpoints. Conclusion: PACS-S appears to be a reliable, valid and clinically meaningful primary endpoint that allows significant improvement over existing endpoints in severe VKC trials. Additional research is needed to validate this endpoint.